Discovery of a Coregulatory Interaction between Kaposi's Sarcoma-Associated Herpesvirus ORF45 and the Viral Protein Kinase ORF36 - Avey, Denis (J Virol, 2016)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of three human malignancies. KSHV ORF36 encodes a serine/threonine viral protein kinase, which is conserved throughout all herpesviruses. Although several studies have identified the viral and cellular substrates of conserved herpesvirus protein kinases (CHPKs), the precise functions of KSHV ORF36 during lytic replication remain elusive. Here, we report that ORF36 interacts with another lytic protein, ORF45, in a manner dependent on ORF36 kinase activity. We mapped the regions of ORF36 and ORF45 involved in the binding. Their association appears to be mediated by electrostatic interactions, since deletion of either the highly basic N terminus of ORF36 or an acidic patch of ORF45 abolished the binding. In addition, the dephosphorylation of ORF45 protein dramatically reduced its association with ORF36. Importantly, ORF45 enhances both the stability and kinase activity of ORF36. Consistent with previous studies of CHPK homologs, we detected ORF36 protein in extracellular virions. To investigate the roles of ORF36 in the context of KSHV lytic replication, we used bacterial artificial chromosome mutagenesis to engineer both ORF36-null and kinase-dead mutants. We found that ORF36-null/mutant virions are moderately defective in viral particle production and are further deficient in primary infection. In summary, our results uncover a functionally important interaction between ORF36 and ORF45 and indicate a significant role of ORF36 in the production of infectious progeny virions. IMPORTANCE Kaposi's sarcoma-associated herpesvirus (KSHV) is a human tumor virus with a significant public health burden. KSHV ORF36 encodes a serine/threonine viral protein kinase, whose functions throughout the viral life cycle have not been elucidated. Here, we report that ORF36 interacts with another KSHV protein, ORF45. We mapped the regions of ORF36 and ORF45 involved in their association and further characterized the consequences of this interaction. We engineered ORF36 mutant viruses in order to investigate the functional roles of ORF36 in the context of KSHV lytic replication, and we confirmed that ORF36 is a component of KSHV virions. Moreover, we found that ORF36 mutants are defective in virion production and primary infection. In summary, we discovered and characterized a functionally important interaction between KSHV ORF36 and ORF45, and our results suggest a significant role of ORF36 in the production of infectious progeny virions, a process critical for KSHV pathogenesis.